Experimental study on property enhancement of potassium Brines with alcohol additives for well completion applications - Ali Naghipour; Ehsan Khamehchi; Javad Mahdavi Kalatehno; Alireza Kazemi (Scientific Reports)
Abstract Well completion operations involve critical post-drilling processes to enable hydrocarbon extraction, where the selection of completion fluids—such as packer, workover, or fracturing fluids—plays a pivotal role in operational success. In Iran’s oil industry, high-temperature, high-pressure reservoirs necessitate high-density brines like calcium bromide. Reservoirs exceeding 300 °F and 10,000 psi (HPHT conditions) typically require completion fluids with densities above 100 lb/ft3. However, economic constraints and limited domestic bromine resources render such fluids prohibitively expensive, while locally available brines often lack essential completion fluid properties. This study addresses these challenges by synthesizing cost-effective, potassium-based brines using domestically sourced salts and alcohols to enhance density and performance. By incorporating alcohols (40% vol.), the crystallization temperature of medium-density brines was significantly reduced, enabling higher salt dissolution and achieving densities of 93.4, 97.8, 99.2, and 99.4 lb/ft3. Alcohol-free variants (93.4 and 97.8 lb/ft3) and alcohol-enhanced formulations (99.2 and 99.4 lb/ft3) demonstrated alkaline pH stability, low viscosity (Viscosity below 70 cP for pumping downhole using available pumps in Iran), minimal clay swelling (< 5 mL/2 g bentonite), and near-zero corrosion rates, even at 300 °F. Notably, exposure to reservoir rock altered wettability from oil-wet to water-wet, enhancing hydrocarbon recovery. Economically, these fluids leverage Iran’s accessible raw materials, offering a 40% cost reduction compared to calcium bromide. Designed primarily as packer fluids, they ensure well integrity under high reservoir pressures while mitigating formation damage. This research presents a scalable, sustainable solution for Iran’s oil sector, balancing technical efficacy with economic viability in challenging downhole environments.